Acceptance Model for Utilizing E-Marketplace Tokopedia with Technology Acceptance Model Among Pekanbaru City Communities - Jushermi, Jushermi; Yelgo Daniel Turnip; Tengku Firli Musfar (West Science Business and Management, 2024)
This research is based on the urgency of understanding how people adopt Tokopedia e-marketplace, utilizing the conceptual framework of the Technology Acceptance Model. The research follows a quantitative approach, with primary data collected used a questionnaire. The study's target population are Tokopedia’s user at Pekanbaru. Non-probability sampling was employed, specifically purposive sampling, with sample criteria including individuals who have engaged in transactions on Tokopedia within the past 3 months, with ages ranging from 17 to 45, and domiciled at Pekanbaru. A total of 100 respondents participated in this study. Path analysis was employed for data analysis using SPSS. Result shown that perceived usefulness has a positive and significant effect toward behavioral intention to use, perceived ease of use has a positive and significant effect toward behavioral intention to use, perceived usefulness has a positive and significant effect toward actual use, behavioral intention to use has a positive and significant effect toward actual use, perceived ease of use has a positive but insignificant effect toward actual use, perceived usefulness has a positive and significant effect toward actual usage through behavioral intention to use, perceived ease of use has a positive but insignificant effect toward actual usage through behavioral intention to use.